PENGARUH PRODUK YANG BERWAWASAN HIJAU TERHADAP MINAT BELI PRODUK AIR MINUM DALAM KEMASAN MEREK ADES - Devi Eprilia Ristanti (Manajemen Bisnis, 2015)
The research purpose’s is to analyze the effect of green-minded products on purchase intention. This research is survey. The research used a questionnaire for collecting data. The result indicated that green-minded product positively influencing purchase intention.